University Marching Band Members’ Noise Dosages and Hearing Health-Related Knowledge - Nilesh J. Washnik (MDPI AG, 2021)
Objectives: (1) To measure sound exposures of marching band and non-marching band students during a football game, (2) to compare these to sound level dose limits set by NIOSH, and (3) to assess the perceptions of marching band students about their hearing health risk from loud sound exposure and their use of hearing protection devices (HPDs). Methods: Personal noise dosimetry was completed on six marching band members and the band director during rehearsals and performances. Dosimetry measurements for two audience members were collected during the performances. Noise dose values were calculated using NIOSH criteria. One hundred twenty-three marching band members responded to a questionnaire analyzing perceptions of loud music exposure, the associated hearing health risks, and preventive behavior. Results: Noise dose values exceeded the NIOSH recommended limits among all six marching band members during rehearsals and performances. Higher sound levels were recorded during performances compared to rehearsals. The audience members were not exposed to hazardous levels. Most marching band members reported low concern for health effects from high sound exposure and minimal use of HPDs. Conclusion: High sound exposure and low concern regarding hearing health among marching band members reflect the need for comprehensive hearing conservation programs for this population.